2020
DOI: 10.1108/mrr-05-2020-0280
|View full text |Cite
|
Sign up to set email alerts
|

Predicting employees’ engagement in environmental behaviours with supply chain firms

Abstract: Purpose The aim of this study is to investigate the employee perceptions of organizational support for environmental behaviours and its impact on innovative environmental behaviours and frequency of involvement in upstream oil and gas supply chain management. The study also examines a new area where environmental work culture has been introduced as a facilitator on the relationship between employees’ perceptions and engagement in supply chain management. Design/methodology/approach Self-administered question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 67 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…The personal attitude of green product consumption is acknowledged by green product orientation ( Paswan et al, 2017 ; Elias, 2020 ). Amin et al (2020) identified a significant relationship between green product orientation and proenvironmental behavior. Yu and Huo (2019) found a positive relationship between green product orientation and green management attitude.…”
Section: Literature Reviewmentioning
confidence: 97%
“…The personal attitude of green product consumption is acknowledged by green product orientation ( Paswan et al, 2017 ; Elias, 2020 ). Amin et al (2020) identified a significant relationship between green product orientation and proenvironmental behavior. Yu and Huo (2019) found a positive relationship between green product orientation and green management attitude.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Firms can employ IEM voluntarily or due to the stern requirements of national and international laws (Acquah et al, 2020;Agyabeng-Mensah et al, 2020a, b, c). However, it is important to emphasize that support from top management or supervisors is very integral if the implementation of IEM will yield its anticipated positive outcomes (Amin et al, 2020). Manifold studies have emphasized the existence and importance of environmental management in various area, spanning from the manufacturing industry (Trujillo-Gallego et al, 2020;Li et al, 2020), service industry (Lucas and Wilson, 2008;Fawehinmi et al, 2020) and mining industry (Kusi-Sarpong et al, 2016).…”
Section: Internal Environmental Management (Iem)mentioning
confidence: 99%
“…According to Savino and Batbaatar (2015), an integrated audit is considered as a core resource for small and medium enterprises. There is no specific way to manage the organisation because it is contingent upon several factors, both internal and external (Amin et al, 2020). Concerning IMS, Zeng et al (2011) found that integrated management effectiveness is a system that provides sustained competitive advantages.…”
Section: Theoretical Foundation and Conceptual Modelmentioning
confidence: 99%